(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The integration of Artificial Intelligence (AI) in healthcare has revolutionized the field, offering substantial improvements in diagnosis, treatment, and patient care. This study aims to explore the multifaceted impacts of AI technologies on healthcare systems, highlighting both the benefits and challenges associated with its adoption. AI applications in healthcare encompass a wide range of functionalities including predictive analytics, medical imaging, personalized medicine, and robotic surgery. Predictive analytics powered by machine learning algorithms enable early disease detection and predictive maintenance of health, reducing hospital readmissions and improving patient outcomes. In medical imaging, AI enhances the accuracy of diagnostic procedures such as MRI, CT scans, and X-rays by detecting anomalies that may be missed by human eyes. Personalized medicine benefits from AI by tailoring treatments based on individual genetic profiles, thereby increasing the efficacy and reducing adverse effects of therapies. AI-driven robotic systems assist surgeons in performing precise and minimally invasive operations, leading to faster recovery times and reduced surgical errors. Natural language processing (NLP) algorithms streamline administrative tasks such as medical documentation and patient data management, allowing healthcare professionals to focus more on patient care.